PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PENGEMBANGAN KARIR SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN LEMBAGA LAYANAN PEMASARAN KOPERASI DAN USAHA KECIL DAN MENENGAH (LLP-KUKM) - Sigit, Suprianto; Efendi, Sugito; Sugiono, Edi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze and prove the direct influence of leadership style, organizationalculture and work discipline on the performance of LLP-KUKM employees, the directinfluence on career development, and the direct influence of career development on theperformance of LLP-KUKM employees, as well as the indirect effect of style. leadership,organizational culture and work discipline on the performance of LLP-KUKM employeesthrough career development. In this study, there was evidence that leadership style and workdiscipline directly had a positive and significant effect on the performance of LLP-KUKMemployees, and had a positive and significant effect on career development, whileorganizational culture had a direct positive and significant effect on the performance ofLLP-KUKM employees but did not. effect on career development. Leadership style, and workdiscipline indirectly have a positive and significant effect on the performance of LLP-KUKMemployees through career development, while organizational culture does not indirectlyaffect the performance of LLP-KUKM employees through career development.